Radikalisme Agama: Dari Kasus Dunia sampai Sumatera Utara - Irwansyah Irwansyah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
After the fall of the World Trade Center (WTC), radicalism has become a religious phenomenon around the world. Uniquely, the Muslims are accused of being perpetrators of such horrible terror. However, it has been unconsciously admitted that the acts and behaviors shown by the Muslims around the world, with special reference to the North Sumatera as the locus of this research, seem to ‘justify’ such accusation. First of all, the acts and behaviors have been started by the feeling of ‘pride’ and ‘happiness’ with the fall of “the twin towers” as the symbol of the USA’s supremacy. The feelings are subsequently coupled by animosity toward the USA and its allies. Such fiery hatred makes the Muslims unable to objectively identify triggering factors behind the emergence of religious radicalism, which, in fact, does not merely exist among the Muslim community but also in every religious community, especially among the Jews and Christians. Regardless of this religious phenomenon, I would argue that there must be another suspicious indicator behind the rise of religious radicalism called ‘destructive theology’. Theology believes that God will be present when humans fight and kill each other. Destruction and burning of worship houses in the North Sumatera are among obvious examples of such theology.